1999
DOI: 10.1159/000014565
|View full text |Cite
|
Sign up to set email alerts
|

Indole Melatonin Agonists and Antagonists Derived by Shifting the Melatonin Side Chain from the C-3 to the N-1 or to the C-2 Indole Position

Abstract: This article reviews our efforts in the development of indole melatonin (MLT) agonist and antagonist compounds. Evidence is presented which indicates that high-affinity melatonergic agonists were obtained by shifting the MLT amido side chain from the C-3 to the N-1 indole position. Conversely, by moving the side chain from the C-3 to the C-2 indole position it is possible to produce MLT antagonist compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The results indicate that this isomer has a similar affinity binding with melatonin membrane receptors as melatonin itself and it also exhibits full agonistic activity in lowering intracellular cAMP levels. In a follow‐up study [100], this group observed that the synthetic MIs induced completely different biological consequences after binding to melatonin membrane receptors. They behaved as agonists or as antagonists depending on the position of the chain A in the indole ring.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that this isomer has a similar affinity binding with melatonin membrane receptors as melatonin itself and it also exhibits full agonistic activity in lowering intracellular cAMP levels. In a follow‐up study [100], this group observed that the synthetic MIs induced completely different biological consequences after binding to melatonin membrane receptors. They behaved as agonists or as antagonists depending on the position of the chain A in the indole ring.…”
Section: Discussionmentioning
confidence: 99%
“…Other fascinating issues regard the biological functions of melatonin isomers and their possible correlation with the healthy potential of red wine. Studies on synthetic isomers showed that the position of the two side chains may affect both receptor‐dependent and receptor‐independent melatonin mechanisms of action, including the binding to melatonin membrane receptors, cytoprotective and antioxidant activities . Interestingly, it was reported that changing the position of either side chain A or side chain M in the indole ring results in marked alteration in isomer antioxidant and cytoprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…Green plants provide both oxygen and nutrients, and some of these nutrients are important antioxidants. In our opinion, in addition to the clinical applications of receptor-mediated actions [15,16,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123], the therapeutic potential of melatonin and analogs [38,[124][125][126] as an antioxidative protective agent [18,19,22,29,30,43,46,72,75,101,[127][128][129][130][131][132][133][134][135][136][137][138] should be further explored.…”
Section: Discussionmentioning
confidence: 99%